Interneuron control of hippocampal oscillations. (April 2015) - Allen, Kevin; Monyer, Hannah
Highlights: Optogenetics and extracellular recordings are now used to study the function of subgroups of hippocampal interneurons for network oscillations. With the help of new juxtacellular recording techniques, the firing properties of anatomically identified interneurons in drug-free animals can be studied. The timing and strength of inhibitory inputs onto different segments of CA1 pyramidal cells vary during theta oscillations and sharp wave/ripples. Abstract : GABAergic interneurons in the hippocampus coordinate neuronal activity that gives rise to network oscillations. In this article we present advances in our understanding of how different classes of hippocampal interneurons contribute to distinct hippocampal network oscillations. We focus on two main experimental approaches that were recently applied in awake animals. Firstly, we review experiments in which selective activation or inhibition of subgroups of GABAergic interneurons was used to asses their contribution to network oscillations. Secondly, we present work that provides a first characterization of the firing activity of anatomically identified interneurons in the hippocampus of behaving animals.